Formation and variability of structural elements of winter wheat yield under controlled environment - Гусенкова, О. В.; Тищенко, В. М. (Scientific Progress & Innovations, 2018)
The article presents the results of four-year researches (2013-2016) on the study of the formation and variability of the main structural element of winter wheat yield – “grain mass from ear” (M1) under controlled environment conditions. As controlled environment three sowing periods were used: early (September 1, TS-1), optimal (September 15, TS-2), late (October 1, TS-3), where TS – terms of sowing. The main purpose of the research was to identify the genotypes of winter wheat, which form the maximum grain mass from the ear, with a high level of stability, regardless of the terms of sowing. In the process of research each year genotypes of winter wheat with a maximum formation level of M1 were selected. Much attention in the analyses was paid to the stability of maintaining the level of formation of the sign “grain mass from ear” of varieties and breeding lines (BL) according to the terms of sowing in order to attract such genotypes into the selection process, where BL is a breeding line. In the experiment of 2013 the stable value of the M1 trait got 11 varieties and 15 BLs, which produced a mass of grain from the ear of 2.00 g (Ivanivska ostysta) to 2.92 g (BL Peremoha 2 × Kolomak 5) × Stanichna) According to the data of 2014, the maximum value of the sign “mass of grain from ear” formed the Sahaidak sort (from 2.40 to 2.87 g) and breeding lines: (Peremoha 2 × Kolomak 3) × Stanichna (2.44-2.62 g), (Sonyachna × Kolomak 5) (2.38-2.77 g), (Erythrospermum × Nakhodka 4) × Stanichna (2.58-2.84 g). In 2015, the high level of stability of the “grain mass of the ear” got 13 varieties and 37 breeding lines of winter wheat, which formed a mass of grain from the ear from 3.00 g to 4.35 g. 20 varieties and 15 breeding lines stably formed the maximum value of the M1 trait according to three periods of sowing. As a result of research it was established that the maximum realization of genotypes of winter wheat on “mass of grain from ear” occurs at early sowing. The varieties and breeding lines of winter wheat, which form the “mass of grain from the ear” with a high degree of stability, are distinguished, regardless of the terms of sowing and with the high adaptation effect on this basis. Genotypes have been identified, which annually, regardless of the terms of sowing, stably formed the maximum value of the “mass of grain from the ear” – BL (Peremoha2 × Kolomak 3) × Stanichna, BL (Peremoha 2 × Kolomak 5) × Stanichna. The genotypes of winter wheat with a high stability manifestation of the “mass of grain from the ear” and high adaptive potential on this basis are recommended as valuable selection material and as parent components in hybridization for the creation of new high-yield winter wheat varieties.